CLASSIC AND MODERN THERAPIES IN PERI-IMPLANTITIS: A REVIEW - Forna Norina; Agop-Forna Doriana (Romanian Dental Association for Education, 2019)
The therapy of peri-implantitis represents a challenge for any dental practitioner and implantology specialist due to the esthetic and functional implications for patients. The classic or modern therapy of peri-implantitis must have three objectives as follows: decrease of bacterial level, implant surfaces detoxification, and regeneration of the peri-implant alveolar bone. Non-surgical therapy alone can be used in early peri-implantitis, but an approach with non-surgical therapy followed by surgical procedures is recommended in moderate or severe peri-implantitis. The decontamination stage can be performed by mixing classic procedures with laser-assisted or photodynamic therapy. The use of laser bio-stimulation can accelerate the healing processes and osseointegration rate. This article reviews classic treatment options and modern treatment procedures used frequently in the management of peri-implantitis.